2021
DOI: 10.1155/2021/2237370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Exposure to L-Band High-Power Microwave on the Brain Function of Male Mice

Abstract: Currently, the impact of electromagnetic field (EMF) exposure on the nervous system is an increasingly arousing public concern. The present study was designed to explore the effects of continuous long-term exposure to L-band high-power microwave (L-HPM) on brain function and related mechanisms. Forty-eight male Institute of Cancer Research (ICR) mice were exposed to L-HPM at various power densities (0.5, 1.0, and 1.5 W/m2) and the brain function was examined at different time periods after exposure. The morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Electromagnetic field radiation, including microwaves, has been classified as a new form of environment pollution that is “possibly carcinogenic to humans” [ 20 ]. Until now, most of the studies have focused on the biological effects and potential mechanisms induced by single-frequency microwaves at the indicated average power density [ 2 , 3 , 21 , 22 ]. However, people are commonly exposed to complex environments with different types of microwaves in daily life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electromagnetic field radiation, including microwaves, has been classified as a new form of environment pollution that is “possibly carcinogenic to humans” [ 20 ]. Until now, most of the studies have focused on the biological effects and potential mechanisms induced by single-frequency microwaves at the indicated average power density [ 2 , 3 , 21 , 22 ]. However, people are commonly exposed to complex environments with different types of microwaves in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years, the biological effects induced by long-term exposure to microwave has been attracting more and more attentions. Our group and others reported that long-term exposure to S band, L band or 900 MHz microwave caused significant pathological injuries in brain and impaired the spatial learning and memory ability [ 2 , 38 , 39 , 40 , 41 ]. Studies also reported that 900 MHz microwave, a classical mobile phone radiation, could disrupt the integrity of blood-brain barrier in rats [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave-induced increase of reactive oxygen species (ROS) is another pivotal mechanism for microwave-biological system interaction [ 8 ]. Studies have demonstrated that microwave-induced biological effects are associated with the frequency, power density, and duration of exposure [ 9 , 10 , 11 ]. Due to the complex environment of the electromagnetic field in our daily life, people are always exposed to microwaves with different parameters.…”
Section: Introductionmentioning
confidence: 99%